Granulomatous lymphadenopathy and tuberculosis: accuracy of histology - Frédéric Méchaï; Lou Macaux; Florence Jeny; Yurdagül Uzunhan; Paul Cioni; Antoine Martin; Nicolas Vignier; Hilario Nunes (International Journal of Infectious Diseases)
Objectives: Due to the insufficient sensitivity of microbiological tests, histology may be helpful for the diagnosis of tuberculosis (TB), especially extrapulmonary TB. Methods: We used the database of the pathology laboratory from 2019 to 2023. We retrospectively analyzed the etiologies of lymph nodes finding epithelioid granuloma and their performance in diagnosing TB. Results: We analyzed the files of epithelioid granulomas for 220 distinct patients. The main etiologies retained were sarcoidosis (n = 110; 50%), TB (n = 86; 39%), and bartonellosis (n = 4; 1.8%). The 74 granulomas with caseous necrosis were distributed between TB (n = 66; 89%), bartonellosis (n = 3; 4.1%), sarcoidosis (n = 2; 2.7%), histoplasmosis (n = 1; 1.4%), or remained undefined (n = 2; 2.7%). For the diagnosis of the 86 TB (55 certain and 31 probable), the caseous necrosis variable had a sensitivity, specificity, positive predictive value, and negative predictive value of 77%, 94%, 89%, and 86% respectively. Conclusions: Histology confirms its accuracy for the diagnosis of TB and allows to quickly initiate a probabilistic treatment for suspected TB without microbiological documentation.